Recovery of electro-mechanical properties inside self-healing composites through microencapsulation of carbon nanotubes - Hasna Hena Zamal (18623362) (2020)
We report the successful microencapsulation of multi-walled carbon nanotubes suspended in a 5-ethylidene-2-norbornene (5E2N) self-healing monomer, into poly melamine urea formaldehyde shells through in situ polymerization. The average size of the microcapsules, their size-distribution, shell wall structural integrity and thickness are characterized by optical and scanning electron microscopy. The presence of carbon nanotubes (CNTs) inside the core liquid content, as well as their release after breaking is confirmed by microscopy and spectroscopy analyses. A small amount of CNTs inside the microcapsules is found to have no significant impact on the thermal stability of the system, as determined by thermogravimetric analysis and differential scanning calorimetry. Both the mechanical and the electrical properties of CNT-based self-healing materials can be restored up to 80% when CNT/5E2N microcapsules are incorporated into polymer composites, thus making them highly suitable for applications in aerospace. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-020-59725-6